Kristalna palača - nov arhitekturni tip javnega prostora - Slivnik, Lara (AR. Arhitektura, raziskave, 2003)
The article deals with the Crystal Palace, the building for the first World Exhibition, held in Londonin 1851. A review is presented about the Building Committee's demands for the architectural competition, Joseph Paxton's proposal, the construction itself, the exhibition and some plans about future use of the building, after the exhibitions closing. Removal of the Palace to Sydenham, as well as some social activities carried out there, are described in detail. The significance of the Crystal Palace is in its' functional architecture, adaptable layout, first use of disassembled construction and glazed façade. The statement about the Crystal Palace stemming from glasshouses and covered railway stations is proven. It is also served as a model for several other buildings, which are mentioned in the article. The culmination in popularity of such buildings was at the end of the nineteenth century when Ebenezer Howard positioned such a building as one of the central buildings in his Garden city scheme. "Crystal palaces" were popular also because they enabled the mixing of social groups, which until then actually never mingled.
Keywords: javne zgradbe; javni prostor; svetovne razstave; Kristalna palača; London; architecture; arhitektura